Clinical profile of acute kidney injury in neonates with perinatal asphyxia - Bhosgi, Revanasiddappa; Harwalkar, Kirankumar (International Journal of Contemporary Pediatrics, 2021)
Background: Acute kidney injury (AKI) is one of the most common complication observed in perinatal asphyxia. Early recognition is required for appropriate treatment and improve the outcome. Methods: It is a hospital based retrospective study conducted from august 2019 to December 2019. Total 85 full term neonates with perinatal asphyxia were included in the study. Renal functions were assessed by monitoring urine output, serum creatinine and ultrasonography. Acute kidney injury assessed by pRIFLE criteria and HIE staging is done by modified Sarnat and Sarnat staging. Severity of AKI is correlated with stages of HIE. AKI is managed as per unit protocol. Results: Total 85 perinatal asphyxia neonates were included in the study. Out of total 85 neonates, 25 (29.4%) neonates had evidence of acute kidney injury. Among 25 neonates with acute kidney injury, higher percentage was observed in male neonates which was 14 (56%) against 11 (44%) among female neonates. Predominantly, non oligouric acute kidney injury was observed among acute kidney injury neonates which accounted to 20 neonates (80%) (p-0.258). Serum creatinine between 1.5-2 mg/dl was observed in 18 (21.1%) neonates and 7 (8.2%) neonates had creatinine between 2-3 mg/dl. Sonological abnormality was noted in 2 (2.3%) neonates. Among neonates with non oligouric AKI, 3 (12%) neonates had HIE stage 1, 15 (60%) had HIE-2 and 7 (28%) had HIE-3. However, neonates with non oligouric AKI were higher among HIE 2 when compared to neonates with oligouric renal failure who were higher in HIE 3. No mortality occurred among these neonates. Conclusions: Majority of the neonates with perinatal asphyxia had non oliguric AKI which responded well to conservative treatment. AKI is most commonly seen in HIE stage 2 babies. Since non oligouric renal failure was a predominant finding among asphyxiated neonates, Serum creatinine monitoring remains main stay of diagnosis.